PEMBUKTIAN MALPRAKTEK DALAM SUATU TINDAKAN MEDIS DOKTER SPESIALIS MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1981 DAN UNDANG-UNDANG NOMOR 20 TAHUN 2025 - Fadler Hidayat; Ardiansah; Andrizal (Smart Education, 2026)
This study aims to analyze the evidentiary system in medical malpractice cases involving specialist doctors under Law Number 8 of 1981 concerning Criminal Procedure Law and Law Number 20 of 2025 and to compare the effectiveness of both systems in providing legal protection for patients. This research is normative legal research employing statutory and comparative approaches, using primary, secondary, and tertiary legal materials analyzed qualitatively. The results show that the evidentiary system under Law Number 8 of 1981 remains limited and formalistic, thus not fully accommodating the complexity of proof in medical malpractice cases which require scientific and professional approaches. Meanwhile, Law Number 20 of 2025 expands the scope of admissible evidence, including electronic and scientific evidence, making it more adaptive to developments in science and technology in the medical field. The comparison indicates a paradigm shift from formal legal certainty toward a balance between legal certainty, justice, and utility. Therefore, the evidentiary regulation under Law Number 20 of 2025 is considered more responsive in handling medical malpractice cases by specialist doctors and provides more optimal legal protection for patients as victims.